Calcium Phosphate Bioceramic Material Local Influence on the Bone Biomechanical Properties at Rabbits with Experimental Osteoporosis - Ananjevs, Vladislavs; Anaņjeva, Aleksandra; Vetra, Janis; Skagers, Andrejs; Salma, Ilze; Locs, Janis; Kasyanov, Vladimir (International Journal of Engineering and Technology, 2018)
Biomechanical characteristics of the rabbit cartilage component from the femur were investigated. The control osteoporosis had been activated by ovariectomy alongside the injections of methylprednisolone. During the experiment defects in the femur’s greater trochanter zone was created and afterwards filled with the fragments of a hydroxyapatite as well as tricalcium phosphate (HAP/TCP 70/30) or HAP/TCP 70/30 mixed with five percent strontium. Three months later animals were euthanazed, squared samples were cut out from the femur’s body and later tested on a bend. The results of the research revealed that the femurs become more stringent after filling off defects in the greater trochanter zone with HAP/TCP 70/30 or HAP/TCP 70/30 mixed with five percent strontium. The ultimate pain for the cartilage component in the control groups was less, than in the test group. The flexure modulus of flexibility of a cartilage component in the test group was statistically reliable less, than the value of the flexure modulus of flexibility of the cartilage component in the control groups.  Therefore, local usage of calcium – phosphatic bioceramic component over the greater trochanter part increases biomechanical characteristics of the cartilage component in the femur of animals.